Continuous Fuel Level Sensor Based on Spiral Side-Emitting Optical Fiber - Chengrui Zhao; Lin Ye; Xun Yu; Junfeng Ge (Journal of Control Science and Engineering)
A continuous fuel level sensor using a side-emitting optical fiber is introduced in this paper. This sensor operates on the modulation of the light intensity in fiber, which is caused by the cladding’s acceptance angle change when it is immersed in fuel. The fiber is bent as a spiral shape to increase the sensor’s sensitivity by increasing the attenuation coefficient and fiber’s submerged length compared to liquid level. The attenuation coefficients of fiber with different bent radiuses in the air and water are acquired through experiments. The fiber is designed as a spiral shape with a steadily changing slope, and its response to water level is simulated. The experimental results taken in water and aviation kerosene demonstrate a performance of 0.9 m range and 10 mm resolution.